Crumpled few-layer graphene: Connection between morphology and optical properties. (September 2021) - Musikhin, Stanislav; Talebi-Moghaddam, Sina; Corbin, Joel C.; Smallwood, Greg J.; Schulz, Christof; Daun, Kyle J.
Abstract: Comprehensive characterization of crumpled graphene materials is required to understand their morphologically dependent properties. This study connects the optical properties of crumpled few-layer graphene (FLG) aerosols and colloidal suspensions with particle morphology. The mass absorption cross-section (MAC) of crumpled FLG was measured in the aerosol phase and it is shown that such aerosols absorb visible light more efficiently than soot aerosols. The UV–Vis spectra of FLG suspensions in ethanol were correlated with the mean nanoparticle layer number and the lateral size. The measured optical properties were also simulated using discrete dipole approximation (DDA) applied to volume-reconstructed particles with refractive indices of graphene and graphite from literature. The measurements were more closely reproduced using the refractive index of graphite pellets rather than flat graphene on a substrate. Moreover, we show that a simpler Rayleigh–Debye–Gans (RDG) model can predict the wavelength dependence of the crumpled FLG absorption cross-section. Graphical abstract: Image 1